ENTROPY ELASTICITY IN POLY(2-HYDROXYETHYL METHACRYLATE) GELS - Dorrington, K; Mccrum, N; Watson, W (1977)
It has been reported that the water-swollen crosslinked poly(2-hydroxyethyl methacrylate) (PHEMA) gel displays an increase of entropy on extension at constant volume in a simple tensile experiment. In this paper, the authors report a new technique for measuring the entropy contribution to tensile load in a solvated polymer. Samples immersed in water at a reference temperature (T//0 equals 30 degree C) are extended to a series of lengths at each of which equilibration with the neighboring solvent is permitted. At each of these lengths, the tensile force is measured as a function of temperature with the sample uptake of water constant by changing the temperature of the sample in a much shorter time than that necessary for changes in water uptake to occur to reestablish osmotic equilibrium at the new temperature. The principle of the experiment is thus the measurement of load at different temperatures at thermal but not osmotic equilibrium. Experimental data are presented and evaluated by using mathematical techniques.